Errors of oral medication administration in a patient with enteral feeding tube - Shahram Emami; Hadi Hamishehkar; Ata Mahmoodpoor; Simin Mashayekhi; Parina Asgharian (Wolters Kluwer Medknow Publications, 2012)
Enteral feeding tube is employed for feeding of critically ill patients who are unable to eat. In the cases of oral medication administration to enterally fed patients, some potential errors could happen. We report a 53-year-old man who was admitted to intensive care unit (ICU) of a teaching hospital due to the post-CPR hypoxemic encephalopathy. The patient was intubated and underwent mechanical ventilation. A nasogastric (NG) tube was used as the enteral route for nutrition and administration of oral medications. Oral medications were crushed then dissolved in tap water and were given to the patient through NG tube. In present article we report several medication errors occurred during enterally drug administration, including errors in dosage form selection, methods of oral medication administration and drug interactions and incompatibility with nutrition formula. These errors could reduce the effects of drugs and lead to unsuccessful treatment of patient and also could increase the risk of potential adverse drug reactions. Potential leading causes of these errors include lack of drug knowledge among physicians, inadequate training of nurses and lack of pharmacists participation in medical settings.